A global analysis of worker protest in digital labour platforms - Ioulia Bessa; Simon Joyce; Denis Neumann; Mark Stuart; Vera Trappmann; Charles Umney (International Labour Organization (ILO), 2022)
This paper presents findings from the Leeds Index of Platform Labour Protest, a database of platform worker protest events around the world which gathers data from online news media reports and other online sources. For the period January 2017 to July 2020, we identified 1,271 instances of worker protest in four platform sectors: ride-hailing, food delivery, courier services and grocery delivery. Our results show that the single most important cause of platform worker protest is pay, with other protested issues including employment status, and health and safety. In most global regions, strikes, log-offs and demonstrations predominated as a form of protest. Furthermore, platform worker protests showed a strong tendency to be driven from below by worker self-organization, although trade unions also had an important presence in some parts of the world. From the four platform sectors examined, ride-hailing and food delivery accounted for most protest events. Although the growth of platform worker organization is remarkable, formal collective bargaining is uncommon, as is formal employment, with ad hoc self-organized groups of workers dominating labour protest across the different sectors, particularly in the global South.
Keywords: 330; decent work; future of work; precarious employment; self employment; digital labour; employment security; conditions of employment; remuneration; labour disputes; trade unions; gig economy; workers rights